2015
DOI: 10.14260/jemds/2015/1451
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Affect of Severity of Exercise on Platelet Function

Abstract: ABSTRACT:Platelets serve an important role in the Physiological process of hemostasis. Platelets also contribute to the formation of pathologic thrombus. Platelet count increases with exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, certain erythrocyte subgroups values were shown to have increased after exercise in several studies [19][20][21]. In addition, several studies reported that platelets count increased with exercise [19,20,[22][23][24][25]. It was also determined that exercise in some cases caused a decrease in the platelet count [16,26].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, certain erythrocyte subgroups values were shown to have increased after exercise in several studies [19][20][21]. In addition, several studies reported that platelets count increased with exercise [19,20,[22][23][24][25]. It was also determined that exercise in some cases caused a decrease in the platelet count [16,26].…”
Section: Introductionmentioning
confidence: 99%
“…Like other blood cells, Plt count may not remain constant and vary to different physiological conditions. From the available studies, intensified exercise was found to increase Plt index during recovery [57][58][59]; although this could not be confirmed in all studies [60,61].…”
Section: Discussionmentioning
confidence: 86%
“…Circulating blood platelets play an important role in the physiological process of hemostasis. It has been documented that exercise training alters the parameters involved in hemostatic, including the number, size, and function of platelets (30). In addition, in a review study, Posthuma et al reported that the hemostatic profile is prominently affected by the intensity of training and is increased more after high-than low-intensity training, as shown by an increase in platelet number and coagulant activity (31).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in platelet count after exercise is the result of the release of fresh platelets from the vascular bed of the spleen and bone marrow in response to increased epinephrine and strong splenic contraction (31). The mechanism of the increase in the MPV variable after exercise training is not yet known but may be due to the secretion of large young platelets from the spleen into the bloodstream (30,31). However, no significant changes in platelet variables (i.e., PLT, MPV, PDW, and PCT) were observed in the present study, suggesting no adverse effect of exercise-related throm-botic events.…”
Section: Discussionmentioning
confidence: 99%